Caring for heart transplant recipients: The lived experience of primary caregivers - Sadala, Maria Lúcia Araújo [UNESP]; Stolf, Noedir Groppo; Bocchi, Edimar A.; Bicudo, Maria Aparecida Viggiani [UNESP] (Elsevier, 2013)
Objective: To understand the experience of primary caregivers of heart transplant recipients. Methods: A phenomenological approach was used to understand the caregivers' experience of caring for a heart transplant patient. In-depth interviews were conducted with 11 caregivers, in a Brazilian hospital, from December 2008 to March 2009. Results: Following the transplant, caregivers' lives change drastically; their priority becomes providing care for their relative. Despite successful transplant results, the uncertainty about future remains, generating permanent distress. Anxiety is exacerbated by familial or economic problems and, consequently, many participants turn to their local communities for support. Some caregivers learn from the experience and plan return to regular activities. Others feel helpless, unable to overcome personal losses and difficulties. Conclusions: Nurses are ideally placed to lead the way by providing family-centered support and education for caregivers of heart recipients. Listening to the concerns of family caregivers seems to be an essential aspect of effective interventions. © 2013 Elsevier Inc.
Keywords: Family caregivers; Heart transplantation; Lived experience; Nursing; Phenomenology; adult; anxiety; Brazil; caregiver; clinical article; economic aspect; female; graft recipient; heart transplantation; human; male; nurse; patient care; priority journal; quality of life; social support; Adaptation, Psychological; Adult; Caregivers; Community Networks; Cost of Illness; Emotions; Female; Health Education; Heart Transplantation; Humans; Life Change Events; Male; Middle Aged; Qualitative Research; Social Support; Stress, Psychological; Uncertainty